Analisis Pengaruh Penerimaan Pajak Daerah Dan Retribusi Daerah Terhadap Pendapatan Asli Daerah Kabupaten/Kota Di Jawa Tengah - Asteria, Beta (JURNAL RISET MANAJEMEN SEKOLAH TINGGI ILMU EKONOMI WIDYA WIWAHA PROGRAM MAGISTER MANAJEMEN, 2015)
This research deals with the impact of Local Tax and Retribution Receipt to Local Government Original Receipt of Regency/City in Central Java from 2008 to 2012. This research utilizes the data of actual of local government budget from Directorate General of Fiscal Balance (Direktorat Jendral Perimbangan Keuangan). Methods of collecting data through census. The number of Regency/City in Central Java are 35. But the data consists of 33 of Regency/City In Central Java from 2008 to 2012. Total of samples are 165. Karanganyar Regency and Sukoharjo Regency were not included as samples of this research because they didn’t report the data of actual of local government budget to Directorate General of Fiscal Balance in 2009.The model used in this research is multiple regressions. The independent variables are Local Tax and Retribution Receipt, the dependent variable is Local Government Original Receipt. The research findings show that Local Tax and Retribution give the significant impact partially and simultaneusly on Local Government Original Receipt at real level 5 percent. All independent variables explain 91,90 percent of the revenue variability while the rest 8,10 percent is explained by other variables.Keywords: Local Tax, Retribution, and Local Government Original Receipt